Efeito da predação de copépodos ciclopóides (Copepoda: Cyclopidae) sobre o tamanho do corpo, razão sexual e comportamento de ovoposição de Aedes albopictus (Diptera: Culicidae) - Cardôso, Helton Charllys Batista (2012)
Cyclopoid copepods have been used as biological agents in successful programs to control mosquito larvae, but the impacts of this predation on adult mosquito populations are still poorly understood. The present study compared the sex ratios and body sizes (measure as wing length) of Aedes albopictus mosquitoes emerging from recipients containing the copepod predator Mesocyclops ogunnus with control situations without this predator. We found that copepod predation significantly biased mosquito sex ratios towards females, and that both the males and females emerging from copepod-containing recipients were significantly larger than control insects. The ecological and epidemiological consequences of the changes induced by copepod predation on mosquito populations are discussed.